Profitabilitas, leverage, inventory intensity ratio dan praktik penghindaran pajak - Nanik Niandari; Fransiska Novelia (Politeknik Ganesha Medan, 2022)
This study was conducted to examine the effect of profitability, leverage, and inventory intensity ratio on tax avoidance practices. The variable of tax avoidance is measured by using the effective tax rate (ETR), the variable of profitability is measured by the return on assets (ROA), the variable of Leverage is measured by the ratio of total debt to total assets, and the Inventory Intensity Ratio is measured by the comparison between total inventory and total assets. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange over a five-year period, namely 2016 - 2020. The number of samples used in this study were 77 companies. The number of final observations used was 245 observations. The sample selection method used is purposive sampling technique. Data were analyzed using multiple linear regression analysis. The type of data used in this study is secondary data in the form of company financial and annual reports which can be downloaded through www.idx.co.id. The results of this study indicate that profitability has a positive effect on tax avoidance practices, inventory intensity ratio has a negative effect on tax avoidance practices, and leverage has no effect on tax avoidance practices. The positive influence of profitability can be a policy input for the government related to good governance practices in companies so that tax avoidance practices can be minimized. This study also found that good inventory management can increase company profits which in turn increase tax revenue for the government. This study was conducted to examine the effect of profitability, leverage, and inventory intensity ratio on tax avoidance practices. The variable of tax avoidance is measured by using the effective tax rate (ETR), the variable of profitability is measured by the return on assets (ROA), the variable of Leverage is measured by the ratio of total debt to total assets, and the Inventory Intensity Ratio is measured by the comparison between total inventory and total assets. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange over a five-year period, namely 2016 - 2020. The number of samples used in this study were 77 companies. The number of final observations used was 245 observations. The sample selection method used is purposive sampling technique. Data were analyzed using multiple linear regression analysis. The type of data used in this study is secondary data in the form of company financial and annual reports which can be downloaded through www.idx.co.id. The results of this study indicate that profitability has a positive effect on tax avoidance practices, inventory intensity ratio has a negative effect on tax avoidance practices, and leverage has no effect on tax avoidance practices. The positive influence of profitability can be a policy input for the government related to good governance practices in companies so that tax avoidance practices can be minimized. This study also found that good inventory management can increase company profits which in turn increase tax revenue for the government.